The Influences of Corporate Governance on Corporate Social Responsibility and Firm Performance of the Listed Companies in Thailand Sustainability Investment - Attarit, Thanapin; Sirimathep, Pilaiporn; Petpairote, Wannuda; Jiracheewee, Jiraporn; Pestunji, Chosita (International Journal of Economics and Financial Issues, 2024)
This study investigates the impact of corporate governance and social responsibility on the financial performance of 149 sustainable stocks listed on the Stock Exchange of Thailand using secondary data from 56-1 reports and employing structural equation modeling (SEM) to assess model fit, the analysis identified several governance factors, such as the proportion of independent directors, board size, and board meeting frequency, as significantly influencing market value. The SEM model demonstrated a strong fit with empirical data (CMIN/df=1.504, CFI=0.990, RMSEA=0.058), with board meeting frequency showing the most significant impact on financial performance at the 0.05 level. The effective corporate governance, particularly in terms of board structure and oversight, is crucial for enhancing the market value of sustainability-focused firms.